Al-WAQF BI JAM'IYYAH MUHAMMADIYAH LAMPUNG - Hilal, Syamsul (Universitas Islam Negeri Raden Intan Lampung, 2015)
Abstract: The Dynamics of Waqaf in Muhammadiyah Lampung. Waqf started in the prophet (pbuh) period and still continues until the present day. The essence of waqf is sharing activity done by the wealthy for the needy managed by nadzir or an institution representing moslem trusted to handle the public asset. Muhammadiyah Lampung complies with the Islamic Law (shariah) as well as the positive Law in Indonesia. There are numerous types of waqf that varies in the form of land, office equipment, waqf for certain professions that are transparent and professionally managed by Muhammadiyah in order to achieve the goal of waqf that is to improve moslem welfare sepecially in terms of education, health service, charity for the needy and orphan children as well as empowering people economy.Abstrak: Dinamika Perwakafan di Muhammadiyah Lampung. Ibadah wakaf dimulai periode Rasulullah Saw., dan masih berlangsung hingga saat ini. Inti tasyrî’ wakaf adalah berbagi kepada pihak yang membutuhkan dari orang kaya kepada orang miskin yang dikelola oleh nadzir atau perwakilan umat Islam yang dipercaya mengelola aset publik. Persyarikatan Muhammadiyah Lampung tunduk pada syari’at Islam dan hukum positif, begitu pula dalam perwakafan. Wakaf berupa tanah, alat perkantoran, profesi tertentu dan lainnya, dikelola secara profesional dan transparan untuk merealisasikan tujuan wakif dalam upaya meningkatkan kesejahteraan umat Islam dalam bidang pendidikan, pelayanan kesehatan, santunan terhadap anak yatim dan dhu’afa serta pengembangan ekonomi kerakyatan.